The Influence of Legal Politics on Economic Development in Indonesia - Sugiono Eksantoso (Universitas Wahid Hasyim Semarang, 2026)
Indonesia is a country rich in abundant natural potential, which can be utilized as a resource and transformed into a potential source of funding to advance and improve the welfare of its people, as well as to develop the national economy—making it an attractive target for other countries in the global market. To meet investor needs, Indonesia is expected to create a conducive climate for the entry of foreign investors so that they continue to serve as a source of revenue for economic development in the country. Law, politics, and economics are key pillars of national economic development, and these three elements must be aligned, harmonious, and synergistic. The direction of legal and political policy in the economic sector holds significant value and benefit, enabling the objectives of the law to be achieved. This is because law is formed and constructed to regulate the economic or business behavior of investors and entrepreneurs. In formulating policies, the political role within the government both executive and legislative is crucial. The resulting legal policies are expected to accommodate all national needs, ultimately ensuring equitable welfare for citizens. At the same time, these policies must also provide space for investors to invest their capital safely, comfortably, and confidently within a stable political environment, thereby supporting the achievement of economic development in Indonesia.